Racial/Ethnic Residential Segregation, Poor Self-rated Health, and the Moderating Role of Immigration - Anderson, Kathryn Freeman (Race and social problems, 2022)
Previous research has demonstrated a relationship between black residential segregation and poor health outcomes. However, this association is less clear for the segregation of other racial/ethnic minority groups in the United States, such as Latinos and Asians. We argue that immigration may moderate this relationship, and that this could help explain these disparate results. We test this using multilevel statistical models of individual-level health data nested within Census tracts in a study of the Houston area using the 2009–2014 Kinder Houston Area Survey, the 2010 U.S. Census, and the 2006–2010 American Community Survey. We find that black and Latino residential segregation is associated with greater poor health reporting, though not for Asian segregation. Further, we find that immigration moderates this relationship for Latino segregation, such that where tract-level immigration is low, Latino segregation is positively related to poor health, but that this slope becomes flatter as immigration increases.